2009
DOI: 10.1093/nar/gkp815
|View full text |Cite
|
Sign up to set email alerts
|

DNA adducts of aristolochic acid II: total synthesis and site-specific mutagenesis studies in mammalian cells

Abstract: Aristolochic acids I and II (AA-I, AA-II) are found in all Aristolochia species. Ingestion of these acids either in the form of herbal remedies or as contaminated wheat flour causes a dose-dependent chronic kidney failure characterized by renal tubulointerstitial fibrosis. In ∼50% of these cases, the condition is accompanied by an upper urinary tract malignancy. The disease is now termed aristolochic acid nephropathy (AAN). AA-I is largely responsible for the nephrotoxicity while both AA-I and AA-II are genoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 48 publications
1
79
0
Order By: Relevance
“…Several recently characterized molecular events, including the intrinsic miscoding properties of dA-AL, in which dAMP is inserted preferentially opposite this lesion during translesion DNA synthesis (27), combine to create the unusual pattern of mutations observed in AA-induced UUC. As with most bulky adducts, dA-AL adducts normally would be excised by global genomic nucleotide excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…Several recently characterized molecular events, including the intrinsic miscoding properties of dA-AL, in which dAMP is inserted preferentially opposite this lesion during translesion DNA synthesis (27), combine to create the unusual pattern of mutations observed in AA-induced UUC. As with most bulky adducts, dA-AL adducts normally would be excised by global genomic nucleotide excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…Site-specific mutagenesis studies in mammalian cells reveal that DNA polymerases frequently incorporate dAMP opposite AL-dA adducts, leading to A-to-T transversions. 43,44 Very recent studies, involving genome-wide sequencing of DNA in tumors of UTUCs from individuals with known exposure to AA, revealed an unusually large number of somatic mutations harboring this uncommon A-to-T transversion attributable to AA. 45,46 Another recent study also reported a high frequency of A–to-T mutations, but also G-to-T transversions as a complementary signature mutation in TP53 of a group of non-smoking women from Belgium who ingested large amounts AA over a short period of time.…”
Section: Metabolic Activation Dna Adduct Formation and Tp53 Mutatiomentioning
confidence: 99%
“…To quantify the 32 P-labeled products, integrated values were measured using a ␤-PhosphorImager and compared with the standards. Because ALI-DNA adducts were not available, a known amount (0.0152 pmol) of ALII-dA-or ALII-dG-modified oligodeoxynucleotides was used as a standard (obtained from Francis Johnson, Department of Chemistry, Stony Brook University) (Attaluri et al, 2010).…”
Section: Metabolism Of [ 3 H]aai In Mouse Livermentioning
confidence: 99%